2006
DOI: 10.1007/s10704-005-3059-z
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic self-affine properties of experimental fracture surfaces

Abstract: Abstract. The scaling properties of post-mortem fracture surfaces of brittle (silica glass), ductile (aluminum alloy) and quasi-brittle (mortar and wood) materials have been investigated. These surfaces, studied far from the initiation, were shown to be self-affine. However, the Hurst exponent measured along the crack direction is found to be different from the one measured along the propagation direction. More generally, a complete description of the scaling properties of these surfaces call for the use of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 26 publications
(30 reference statements)
5
64
0
Order By: Relevance
“…This scaling, referenced to as Family-Viscek scaling [22], corresponds precisely to the one exhibited -at different length-scales but with the similar scaling exponents ζ, β and z = ζ/β -by heterogeneous materials [5,6]. Table I., a collapse of the data on a single curve is readily obtained…”
Section: B Determination Of the Direction Of Crack Propagation/crackmentioning
confidence: 56%
See 2 more Smart Citations
“…This scaling, referenced to as Family-Viscek scaling [22], corresponds precisely to the one exhibited -at different length-scales but with the similar scaling exponents ζ, β and z = ζ/β -by heterogeneous materials [5,6]. Table I., a collapse of the data on a single curve is readily obtained…”
Section: B Determination Of the Direction Of Crack Propagation/crackmentioning
confidence: 56%
“…As a matter of fact, it has been recently shown [5,6] that a complete description of the scaling properties of fracture surfaces in heterogeneous materials like e.g. glass, metallic alloy, wood or mortar calls for the use of the 2D height-height correlation function.…”
Section: B Determination Of the Direction Of Crack Propagation/crackmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33][34] The previous studies have shown that the real fracture surfaces can be described by fractal geometry obeying the self-affine scaling fractal law. 35,36 This is of great help in many cases since it provides a numerical method to generate the fracture surface that mimic rough characteristic of natural rock fractures.…”
Section: Fracture Surface Propertiesmentioning
confidence: 99%
“…These fluctuations of G I dc are associated to the surface roughness and, more precisely, to the amount of created surface A r which varies significantly during fracture propagation (Kopp et al 2014a;Fond and Schirrer 2001;Osovski et al 2015;Srivastava et al 2014). Since the estimation of the amount of created fracture surface is typically a scale dependent measurement (Bouchaud 1997;Candela et al 2012), a multi-scale approach has to be considered (Deumié et al 1996) and several models exist to characterize this complex geometry (Mandelbrot et al 1984;Lopez and Schmittbuhl 1998;Ponson et al 1992;Bouchaud et al 1995).…”
Section: Introductionmentioning
confidence: 99%